2020
DOI: 10.21595/jve.2020.21373
|View full text |Cite
|
Sign up to set email alerts
|

The inner product vector as an output-only cross-correlation-based feature to structural damage assessment

Abstract: This paper presents a structural damage assessment method that relies on a crosscorrelation-based damage sensitive feature known as Inner Product Vector (IPV). Such a feature is extracted from the dynamic response measured at different locations within a structure. Previous investigations on the use of the IPV in a damage detection framework were conducted through laboratory tests by manipulating the excitation source in an input-output approach. In this paper, a new output-only approach has been developed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Among the non-destructive techniques, vibration-based methods have gained prominence due to their sensitivity to changes in stiffness and dynamic characteristics of the structure [14,[21][22][23]. Vibration-based methods involve exciting the structure with a known input signal and analysing the response to extract information about its stiffness, damping, and natural frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Among the non-destructive techniques, vibration-based methods have gained prominence due to their sensitivity to changes in stiffness and dynamic characteristics of the structure [14,[21][22][23]. Vibration-based methods involve exciting the structure with a known input signal and analysing the response to extract information about its stiffness, damping, and natural frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…This lowers the cost of construction but leads to an increase in the value of installation errors and expert control. There are many studies connected to searching the criteria for assessing buildings technical condition [4][5][6][7][8][9]. The main conclusion is that expert tests are necessary and relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Determining dynamic criteria for assessing structural health is a critical and difficult task since many factors are affecting the system dynamics in various conditions [9]. Recently, a large number of works have appeared on structure dynamics separately and the entire building as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Mohammad used the cross-correlation damage index to determine the damage locations in the length of continuous deck bridges, and a comparison of the obtained analytical results with the experimental results showed that the proposed methods can determine the damage locations with appropriate accuracy for different damage scenarios [10]. Morgantini and Betti presented a structural damage assessment method that relies on a cross-correlation-based damage-sensitive feature, which is extracted from the dynamic response measured at different locations within a structure [11]. Li and Huang proposed an approach to identify structural states from eigenvectors constructed using cross-correlation functions.…”
Section: Introductionmentioning
confidence: 99%